Sulfur affects root growth and improves nitrogen recovery and internal efficiency in wheat - Carciocchi, Walter Daniel; Divito, Guillermo Adrián; Fernández, Lucrecia A.; Echeverria, Hernan Eduardo (2017)
Wheat plants were cultivated in pots with the objective of evaluate the effect of two sulfurrates (+S and -S) on i) shoot growth, S and nitrogen uptake and nitrogen use efficiency(NUE) and ii) root growth and architecture and its relations with sulfur and nitrogen uptake. Plant samplings were at Z39, Z51 and Z92 stages. Shoot mass and NUE were greater in +S treatment at the three stages. –S plants increased root growth at Z39 (14% more length and 16% more tips) in comparison with +S, but the opposite occurred at Z51 (31% less area and 42% less mass). Sulfur uptake per unit root mass, area and length were greater in +S treatment at Z39 and Z51. A similar pattern was determined for nitrogen uptake at Z39, but the opposite occurred at Z51. This indicates that nitrogen uptake is mainly controlled by shoot growth and not by root growth